The transfigured kingdom : sacred parody and charismatic authority at the court of Peter the Great - Zitser, Ernest A. (Cornell University Press, 2004)
The author suggests that by implicating Peter's "royal priesthood" in taboo-breaking, libertine ceremonies, the organizers of such "sacred parodies" inducted select members of the Russian political elite into a new system of distinctions between nobility and baseness, sacrality and profanity, tradition and modernity." "Tracing the ways in which the tsar and his courtiers appropriated aspects of Muscovite and European traditions to suit their needs and aspirations, The Transfigured Kingdom offers one of the first discussions of the gendered nature of political power at the court of Russia's self-proclaimed "Father of the Fatherland" and reveals the role of symbolism, myth, and ritual in shaping political order in early modern Europe."--Jacket